Efficient Hydrolysis of Ammonia Borane for Hydrogen Evolution Catalyzed by Plasmonic Ag@Pd Core–Shell Nanocubes - Xu, Peng; Lu, Weiwei; Zhang, Jinjin; Zhang, Li (ACS sustainable chemistry & engineering, 2020)
Developing an efficient catalyst for H2 generation from hydrolysis of ammonia borane (AB) in a controllable and sustainable way is a prerequisite to implementing H2 as an alternative energy vector. To meet this requirement, the present work designs and constructs a potential Ag@Pd core–shell catalyst, in which the plasmonic Ag nanocube core acts as a light absorber and the ultrathin Pd shell as the actively catalytic site. First, the core–shell structure of the prepared Ag@Pd samples is characterized and confirmed by an electron microscope and energy dispersive spectroscopy. Then their catalytic performances for AB hydrolysis are investigated and compared with Ag nanocubes under the light on/off condition and at different temperatures. The results show that the H2 generation rate on Ag@Pd is greatly enhanced, which is found to benefit from the reduced activation energy under light illumination. Further investigation of wavelength-dependent performance verifies the plasmon-driven nature of the Ag@Pd catalysts. The subsequent optical simulation using the finite element method indicates that the absorbed light energy is instead preferential to dissipate into the nonplasmonic but catalytic Pd site when the Pd shell coats on the plasmonic Ag nanocube. This leads to the concentration of energetic charge carriers in the outer Pd shell and thus the much higher catalytic efficiency of Ag@Pd core–shell catalyst than its single compartment for breaking down the N–B bond of AB to produce H2 gas.